Gaya Retorika Channel YouTube Okky Adams sebagai Media Edukasi dalam Membuat Motor Custom Chopper - Maksum, Ahmad Pucuk (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Rhetorical style is a style or art of speaking, either achieved based on natural talent or through technical skills. The art of speaking does not only mean speaking fluently without a clear and contentless way of thinking, but an ability to speak and make speeches in a short, clear, concise and impressive manner. The purpose of this research is to understand how the rhetorical style affects the content carried out by Okky Adam on the Okky Adams YouTube channel as an educational medium in making custom chopper motorcycles and what obstacles are when creating educational content on the Okky Adams YouTube channel as an educational medium in making custom chopper motorcycles. This research uses classical rhetorical theory. The research uses a descriptive qualitative method by interviewing 6 informants, namely, Okky Adam Saputra as the key informant and the other 5 are subscribers of Okky Adams' YouTube channel, namely, Henry Dwi Prasetya, Boby Samosir, Raffy Rabbani Sanu, Okta Saputra, Ahmad Zidan Fauzan. The data collection techniques carried out in the research are observation, interviews, and documentation. The results of this study show that the rhetorical style on Okky Adams' YouTube channel as an educational medium in making custom chooper motorcycles has a great impact on the audience.